Academic Model Supervision on Behavior Protection Behavior in the Hazards of Biologic Agents in Regional General Hospital dr. Doris Sylvanus Palangka Raya - Mimin Lestari (Healthy-Mu Journal, 2023)
Safety is one of the quality of service so to improve the quality of the hospital it is important to pay attention to safety behavior. RSUD dr. Doris Sylvanus Palangka Raya has a mission to improve the development of hospital resources in accordance with the quantity and quality. To describe the self-protective behavior of nurses against the dangers of biological agents before applying supervision of the academic model and after applying supervision of the academic model. This research method used a quasi-experimental pre and post test control group design with a total sample of 70 people with details of 35 nurses in the intervention group and 35 people in the control group. The description of the characteristics of the implementing nurses in this study were that the majority were female, working experience of more than 3 years, age <35 years. There was a change in Nurse Safety Behavior on the Hazards of Biological Agents between before and after the Academic Model Supervision Intervention. The supervision method is considered capable of changing the safety behavior of nurses and influencing nurses to behave well in safety against the dangers of biological agents.